The Effect of Extra Virgin Olive Oil (EVOO) on Fetal Birth Weight in Preeclampsia Rat Model - Silvani, Yulia; Maharani, Afniari; Lovita, Agnestia Naning Dian (Fakultas Kedokteran Universitas Brawijaya, 2020)
Preeclampsia, as one of the most common pregnancy-specific diseases, causes high maternal-fetal morbidity and mortality in almost every country. Placental vascular abnormalities in preeclamptic women can cause chronic hypoxia and impaired fetal nutrition, so fetal growth retardation often occurs. EVOO has strong antioxidant effect is assumed to prevent nutritional disorders in the fetus. This study aimed to determine the effect of EVOO on fetal birth weight in a preeclampsia rat model. This research was laboratory research conducted in vivo with a Post Test Only Control Group design which consisted of five groups; negative control group, positive control group (pre-eclampsia rat model), dose 1, 2, and 3 groups that were preeclampsia rats given EVOO in 3 different doses (0.5 mL/day, 1 mL/day and 2 mL/day respectively). Blood pressure and proteinuria measurements were carried out at the 12, 15 and 19 day of pregnancy. After sacrificed, fetal weight was measured immediately using analytical balance. The result of this study showed that there was a significant reduction of fetal weight between negative control and positive control group (p=0.020), meanwhile no significant differences among positive control, dose 1 and dose 2 group (p=0.90 and p=0.142) but statistically significant to dose 3 group (p=0.005). EVOO administration increases fetal weight in doses group by its AA and DHA in Long-Chain Poly Unsaturated Fatty Acids (LCPUFA) within. The optimal dose of EVOO to increase fetal weight is 2 mL/day.